Systematic review: diet–gene interactions and the risk of colorectal cancer. Issue 4 (10th December 2012) - Andersen, V.; Holst, R.; Vogel, U.
Summary Background Diet contributes significantly to colorectal cancer (CRC) aetiology and may be potentially modifiable. Aim To review diet–gene interactions, aiming to further the understanding of the underlying biological pathways in CRC development. Methods The PubMed and Medline were systematically searched for prospective studies in relation to diet, colorectal cancer and genetics. Results In a meta‐analysis, no interaction between NAT1 phenotypes and meat intake in relation to risk of CRC was found (P‐value for interaction 0.95). We found a trend towards interaction between NAT2 phenotypes and meat intake in relation to risk of CRC. High meat intake was not associated with risk of CRC among carriers of the slow NAT2 phenotype, whereas NAT2 fast acetylators with high meat intake were at increased risk of CRC (OR = 1.25; 95% confidence interval (CI): 0.92–2.01) compared with slow acetylators with low meat intake (reference), P‐value for interaction = 0.07. Low meat intake in the studied populations may influence the result. Interactions between meat, cruciferous vegetables, fibres, calcium, vitamins, and alcohol and ABCB1, NFKB1, GSTM1, GSTT1, CCND1, VDR, MGTM, IL10 and PPARG are suggested. Conclusions A number of interactions between genetic variation and diet are suggested, but the findings need replication in independent, prospective, and well‐characterised cohorts before conclusions regarding the underlying biological mechanisms can be reached. When the above criteria are met, studies on diet–gene interactions may contribute valuable insight into the biological mechanisms underlying the role of various dietary items in colorectal carcinogenesis.